1984
DOI: 10.1007/bf00495956
|View full text |Cite
|
Sign up to set email alerts
|

Butyl hydroxy toluene antagonizes the gastric toxicity but not the pharmacological activity of acetylsalicylic acid in rats

Abstract: Butyl hydroxy toluene reduced gastric erosion due to acetylsalicylic acid in the rat, but not the antiinflammatory, anti-pyretic and analgesic activity. By itself, BHT exhibited activity only in the test on analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Such a concept is supported by a wealth of literature, much of which preceded these findings on leukocyte adhesion, that demonstrated the protective actions of broad range scavengers of oxygen reactive species, on NSAID-induced gastric injury [38][39][40][41]. Such a concept is supported by a wealth of literature, much of which preceded these findings on leukocyte adhesion, that demonstrated the protective actions of broad range scavengers of oxygen reactive species, on NSAID-induced gastric injury [38][39][40][41].…”
Section: Mucosal Blood Flowmentioning
confidence: 81%
See 2 more Smart Citations
“…Such a concept is supported by a wealth of literature, much of which preceded these findings on leukocyte adhesion, that demonstrated the protective actions of broad range scavengers of oxygen reactive species, on NSAID-induced gastric injury [38][39][40][41]. Such a concept is supported by a wealth of literature, much of which preceded these findings on leukocyte adhesion, that demonstrated the protective actions of broad range scavengers of oxygen reactive species, on NSAID-induced gastric injury [38][39][40][41].…”
Section: Mucosal Blood Flowmentioning
confidence: 81%
“…The mechanism by which adhering neutrophils could initiate mucosal injury through actions on the microcirculation may involve the release of cytotoxic radicals such as superoxide, following activation of the cells during the process of adherence. Such a concept is supported by a wealth of literature, much of which preceded these findings on leukocyte adhesion, that demonstrated the protective actions of broad range scavengers of oxygen reactive species, on NSAID-induced gastric injury [38][39][40][41]. The role of the local release of free radicals in the tissue damage induced by aspirin or indomethacin has been evaluated in early work by a number of inorganic free-radical scavengers [40] as well as by systemic infusion of superoxide dismutase and catalase [41].…”
Section: Mucosal Blood Flowmentioning
confidence: 90%
See 1 more Smart Citation
“…Certain free radical scavengers, e.g., sulfhydryl agents (23), butylated hydroxytoluene (24), and (+) cyanidanol (25), have been reported to offer protection against several experimental gastric lesions. These reports suggest that toxic free radicals which result in lipid peroxidation may play an important role in the pathogenesis of gastric injuries.…”
Section: Resultsmentioning
confidence: 99%
“…In support of this suggestion, recent studies have shown that administration of LT antagonists or 5-LO inhibitors markedly reduces the gastric ulcerogenicity of indomethacin and other NSAIDs in mice treated with the cholinomimetic, bethanechol chloride (46). This evidence, combined with observations that 1) dual CO-LO inhibitors cause less gastric mucosal damage than CO inhibitors of equal anti-inflammatory potency (1 3,47, 70), and 2) that antioxidants (e.g., butyl hydroxytoluene) which scavenge oxygen radicals can inhibit gastric lesions induced in rats by CO inhibitors (43,67), suggests that the diversion of arachidonic acid by the inhibition of CO by NSAIDs could have dual consequences. Hence, there could be effects from the relative excess of LO products produced from this inhibition of CO activity as well as loss of endogenous gastroprotective capacity from the deficit of PGs.…”
Section: Mechanisms Of Gastric Mucosal Damagementioning
confidence: 88%